A pectic polysaccharide in seed gum of Lepidium campestre - Manneteg, Anna (SLU/Department of Molecular Sciences, 2017)
Lepidium campestre (field cress) is an oilseed species with a great potential of becoming a new commercial crop in Sweden. As the oil is being extracted from the crop, the residual from the extraction is left in form of a seed cake. As this seed cake is soaked in water a gel is formed around the seeds. The purpose of this paper was to study the chemical composition of the seed gum extracted from L. campestre and to examine if a possible field of use exist for this substance. The seed gums function is tested, but no real rheological study is executed and no study is done on the seed itself. In this study, there is only one kind of seeds from one harvest analysed and different kinds of varieties within the species L. campestre are not studied. The seed gum was separated from the seeds and freeze-dried before analysed. The determined molecular weight was 50-100 kDa, measured with Multi-Angel Light Scattering. The measured absorbance in light absorbance spectrum resulted in a detected substance at a wavelength of 280 nm, indicating aromatic amino acids in protein. This however was in a very small concentration. Determination of soluble dietary fibre was preformed according to The Uppsala Method, determination of neutral sugar residues by gas chromatography and for uronic acid by spectrophotometry. To further understand the structure of the seed gum, 1H NMR spectroscopy was performed. The seed gum was consisting of up to 80 % dietary fibre and with a total yield of 7 % from weight seeds. The results showed that the seed gum consist of a high proportion of uronic acid, galactose and rhamnose - a rhamnogalactouronic pectic substance. The pectin contributes to a very stable and reliable seed gum that could be widely used in the food industry. Possible fields of applications are e. g. as dietary fibre-enrichment in food products or production of gluten-free bread which is tested in this study. In this thesis, it is proven that it is a very easily extractable and easily isolated substance that does not have any smell and most likely no taste. From L. campestre, it is possible to get a substance made of a up to 80 % pure pectic substance, and all that is required is water and a mixer.